Pre-service Teachers' Concept of Sustainable Development and Its Integration in Science Lessons - Darryl Roy T. Montebon (Universitas Negeri Malang, 2018)
Abstract: Sustainable development is a "durable development" that is systematic and long-term devel-opment of countries ensuring strong relationship between societal and environmental security with economic progress. The concept of sustainable development is essential for pre-service teachers to realize because the country is on its way to progress and industrialization and their role as future teach-ers is important. Hence, this paper investigates aims to determine pre-service teachers' concept of sus-tainable development. It is important that the concept of sustainable development should be clear to teachers because it determines how effective they can teach the concept to their students.  A qualitative research design utilizing questionnaires, interviews, and focused group discussions reveal the miscon-ceptions of the pre-service teachers on sustainable development.  The result of the present research will be utilized to create a program that will assist them in preparing lessons that integrates the concept of sustainable development successfully. Key Words: misconceptions on sustainable development, pre-service teachers concept of sustainable development, integration of the sustainable development concept on science lessons Abstrak: Pembangunan berkelanjutan adalah "pembangunan tahan lama" yang merupakan pembangun-an sistematis dan jangka panjang negara untuk menjamin hubungan yang kuat antara keamanan sosial dan lingkungan dengan kemajuan ekonomi. Konsep pembangunan berkelanjutan penting bagi calon guru untuk diwujudkan karena negara sedang dalam proses untuk kemajuan dan industrialisasi serta peran mereka sebagai guru masa depan sangatlah penting. Oleh karena itu, tulisan ini menelaah konsep pembangunan berkelanjutan calon guru. Sangatlah penting bahwa konsep pembangunan berkelanjutan calon guru harus sangat jelas karena hal itu menentukan seberapa efektif mereka dapat mengajarkan konsep kepada siswa mereka. Sebuah desain penelitian kualitatif menggunakan kuesioner, wawancara, dan diskusi kelompok terfokus mengungkapkan kesalahpahaman dari guru calon pada konsep pemba-ngunan berkelanjutan. Hasil dari penelitian ini akan digunakan untuk membuat sebuah program yang akan membantu mereka dalam mempersiapkan pelajaran yang mengintegrasikan konsep pembangunan berkelanjutan dengan berhasil. Kata kunci: kesalahpahaman pembangunan berkelanjutan, konsep pembangunan berkelanjutan calon guru, integrasi konsep pembangunan berkelanjutan pada pembelajaran sains